Legal Review of Specimen Collection for DNA Testing Without the Sample Owner's Authorization - Darto Darto; Abdul Kolib; Handoyo Prasetyo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
In the modern legal system, Deoxyribonucleic Acid (DNA) testing has become an important tool in the resolution of criminal and civil cases in Indonesia. The use of DNA can assist in determining blood relations, uncovering sexual abuse cases, and proving involvement in other crimes. Nonetheless, there are various legal issues that arise regarding the collection of DNA specimens without the consent of the sample owner. In Indonesia, although there are personal data protection regulations such as the Health and Population Administration Law, there are no specific provisions regarding the legality of unauthorized DNA sampling. This creates uncertainty in the legal system, especially in terms of evidence being recognized in court. Unauthorized DNA sampling can violate an individual's right to privacy guaranteed by the 1945 Constitution and the Criminal Procedure Law. This potentially makes DNA test results inadmissible as valid evidence in court. Therefore, this study aims to analyze the legality of the practice of unauthorized DNA sampling and its impact on the legal evidentiary system in Indonesia. The study also highlights the importance of medical ethics and legal protection of privacy in determining the validity of DNA evidence in judicial proceedings. It also explores the role of medical ethics and privacy law in determining the validity of DNA test results in the judicial process, and provides recommendations for clearer regulations regarding DNA sampling procedures.